2022
DOI: 10.1186/s12870-022-03617-6
|View full text |Cite
|
Sign up to set email alerts
|

RAD-seq as an effective strategy for heterogenous variety identification in plants—a case study in Italian Ryegrass (Lolium multiflorum)

Abstract: The primary approach for variety distinction in Italian ryegrass is currently the DUS (distinctness, uniformity and stability) test based on phenotypic traits. Considering the diverse genetic background within the population and the complexity of the environment, however, it is challenging to accurately distinguish varieties based on DUS criteria alone. In this study, we proposed the application of high-throughput RAD-seq to distinguish 11 Italian ryegrass varieties with three bulks of 50 individuals per varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The analysis performed in this study confirmed the suitability of the GBS method used. As supported by previous research [31,32,34,35], the restriction site-associated DNA sequencing method is a reliable tool for genotyping crop species. Genotyping-by-sequencing through RADseq and SNP markers has many possible applications for breeders in MAB, MAS, or PVP purposes.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The analysis performed in this study confirmed the suitability of the GBS method used. As supported by previous research [31,32,34,35], the restriction site-associated DNA sequencing method is a reliable tool for genotyping crop species. Genotyping-by-sequencing through RADseq and SNP markers has many possible applications for breeders in MAB, MAS, or PVP purposes.…”
Section: Discussionmentioning
confidence: 79%
“…The RADseq approach proved to be suitable for reconstructing the genetic structure of a breeding core collection, highlighting genomic information about the ancestral genotypes of different lines, and analysing interspecific hybrids. Moreover, through the use of related species' assembled genomes, crop comparative analyses can be performed to exploit new genetic resources, which can be adopted for many breeding and traceability purposes, as already demonstrated in other studies [16,32,46,47]. Moreover, the CAPS marker for male-sterility characterization discussed here has proven its reliability and its possible application in breeding planning, as well as its associated RADtag_2329, which can be used in future wide-spectrum GBS approaches in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many GBS-related techniques that differ in the sequencing platform, the chemistry they are based on, the type of output, data throughput and other aspects [ 24 , 25 , 26 , 27 , 28 , 29 ]. Among the available GBS approaches, restriction-site associated DNA sequencing (RADseq) [ 30 ] has demonstrated its potential use in different crop species for breeding, PVP and traceability purposes [ 16 , 31 , 32 ]. Among the several advantages provided by the adoption of this approach is the unnecessity of an already sequenced genome because a comparative analysis between the sequenced reads can be made even without mapping them onto chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the SSR assay is easily performed by PCR, a method that does not require specific and expensive laboratory equipment. Despite the recent development of next-generation sequencing (NGS) techniques, particularly restriction site-associated DNA sequencing (RAD-seq) [ 15 ] and genotyping-by-sequencing (GBS) technologies, such as genotyping by random amplicon sequencing and direct (GRAS-Di) [ 16 ], we want to provide a molecular assay that is less costly and time-consuming and that could be practically applied by small laboratories of seed companies. From the literature, the use of molecular markers in the evaluation of the genetic diversity of L. multiflorum accessions has been reported by few studies using sequence-related amplified polymorphisms (SRAPs) [ 17 ], randomly amplified polymorphic DNA (RAPD) [ 18 ], and SSRs combined with bulk strategies [ 19 ].…”
Section: Introductionmentioning
confidence: 99%